IDENTIFICATION OF BIOMARKERS OF RENAL PARENCHYMA DAMAGE IN THE URINE OF PATIENTS WITH CHRONIC PYELONEPHRITIS BY ELISA AND MASS SPECTROMETRY METHODS - N. B. Zakharova; L. Kh. Pastushkova; R. V. Lakh; I. M. Larina; E. N. Nikolaev; A. N. Ponukalin; N. A. Varaksin; V. I. Оficerov; A. S. Kononikhin (Медицинская иммунология, 2019)
We performed clinical observations and laboratory examination of 22 patients with chronic pyelonephritis (chronic renal failure, CRF) and 30 healthy individuals. The patients with CRF were examined twice. The first group (Group I) included patients with exacerbation of the disease. The comparison series (Group II) was represented by the same patients who were examined 1.5-3 months after completion of treatment, without clinical exacerbation of chronic pyelonephritis (CPN). Laboratory signs of acute renal damage were not detectable in all the patients examined. Concentrations of VEGF, MCP-1, IL-8 and IL-18 were determined in urine samples of all examined persons by ELISA technique. Protein spectrum of urine was assessed in six patients from Group I, and in six cases of Group II by means of mass spectrometry, using Agilent 1100 chromatographic device, and LTQ-FT Ultra hybrid mass spectrometer. The results of parallel determination of urine proteins by the two methods have shown that the evolving CPN exacerbation is associated with local secondary immune deficiency at the level of renal tubular urothelium. Determination of urine proteome by means of mass spectrometry in exacerbating disease allows identify the proteins associated with damage to epithelial lining of renal tubules and development of local immune response.